Asphalt Concrete Overlay Optimization Based on Pavement Performance Models - Jan Mikolaj; Lubos Remek; Marian Macula (Advances in Materials Science and Engineering)
The life cycle length of pavement with asphalt concrete material (ACM) surfacing is significantly influenced, in addition to transport loading and climatic conditions, by design method and rehabilitation timing. Appropriate overlay thickness calculation and estimation of optimal rehabilitation time are crucial to maximizing life cycle length and, concurrently, reducing road administration costs and road user costs. This article describes a comprehensive method of ACM rehabilitation design. For optimization of life cycle cost analysis (LCCA) based design, mathematical analytical solution in combination with experimental verification of physical, mechanical, and fatigue characteristics is utilized. Pavement performance, that is, functions mathematically describing pavement’s degradation characteristics of operational capability, is represented by longitudinal and transverse unevenness; these are used to describe relations between traffic loading and pavement’s bearing capacity on 1 : 1 scale. Optimizing of rehabilitation plan is carried out by making a cost benefit analysis (CBA) for several rehabilitation scenarios in which different rehabilitation timing produces different capital cost requirements and social benefits. Rehabilitation scenarios differ in technology, the design of which needs to be mathematically optimized, and timing of rehabilitation execution. This article includes a case study for the sake of illustration of practical results and verification of applicability of used methodology.